Analysis of Social Values in The Film Atap Padang Mahsyar by M. Dedy Vansophi - Wulan Defi Prawesti; Raras Hafiidha Sari (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research was prepared with the aim of describing the social values contained in the film entitled "Atap Padang Mahsyar" by M. Dedy Vansophi. This research is research that uses a qualitative descriptive method, which is further explained by describing it with text. The data source was produced in the film Atap Padang Mahsyar, which was collected using research analysis through literature review, direct observation techniques in the film, as well as through note-taking techniques in the form of pictures in important parts of the film. The research was also carried out with a literary sociology approach to make it easier for researchers to compare problems in films and social problems that correspond to the realities of today's society. Through research on social problems in films, researchers found social values that can be benefited from, one of which is caring, mutual help, mutual cooperation, deliberation, responsibility and devotion.